Modern spiritualism in Italian literature and culture (1765-1969) - Ambrosino, Gennaro; Camilletti, Fabio; Van den Bossche, Bart (Warwick series in the humanities, 2026)
"In reconstructing the history of Modern Spiritualism, scholars have largely focused on its Anglo-American, French, and German developments, often overlooking the Italian context. Modern Spiritualism in Italian Literature and Culture (1765-1969) challenges this perspective by examining the Italian case as a space of intersection between transnational currents of thought and deeply rooted cultural traditions. From the Enlightenment to the occult revival of the 1960s, Modern Spiritualism in Italy engaged with scientific discourse, philosophical speculation, literary imagination, and Catholic doctrine, producing a hybrid intellectual landscape that remains largely understudied. This volume traces the circulation and transformation of spiritualist ideas across different media and disciplines, analyzing their impact on literature, psychology, and science. By situating Italy within the broader European and transatlantic networks of occult knowledge, Modern Spiritualism in Italian Literature and Culture provides a new vantage point from which to rethink the historical evolution of modernity, belief, and the supernatural"